Sustainability-Based Islamic Corporate Governance and Islamic Banks’ Multi-Performance: Evidence from Indonesia - Irna Puji Lestari; Mamduh Mahmadah Hanafi; Leo Indra Wardhana (Bank Indonesia, 2025)
This study develops a Sustainability-based Islamic Corporate Governance (SICG) index that integrates the roles of the Shariah board, regular board, and sustainable board and examines how it impacts multi-dimensional performance of Islamic banks. It employs a sample of 15 Islamic commercial banks in Indonesia from 2010 to 2023. The findings reveal that governance elements have a positive impact on particularly financial performance, while its influence on social performance is limited. For environmental and sustainability performance, a positive impact is primarily observed in the roles of the regular and sustainable boards. Further analysis through the Paris Agreement interaction confirms that most of these findings are consistent and support the role of SICG in enhancing various performances of Islamic banks. These results highlight the need for Islamic banks in Indonesia to transition toward SICG and suggest that policymakers facilitate this transformation by developing relevant regulations and guidelines to align governance structures with broader sustainability objectives. Acknowledgment The paper is supported by sponsorship from the Indonesia Endowment Fund for Education (LPDP), whose sponsorship has played a crucial role in facilitating the research process. The authors deeply appreciate this support and are grateful for the opportunities it has provided. The authors also gratefully acknowledge the valuable comments provided by the journal's editors and reviewers.